Delirium in acute stroke: A prospective, cross‐sectional, cohort study. (10th February 2021) - Rollo, Eleonora; Callea, Antonio; Brunetti, Valerio; Vollono, Catello; Marotta, Jessica; Imperatori, Claudio; Frisullo, Giovanni; Broccolini, Aldobrando; Della Marca, Giacomo
Abstract: Background and purpose: Delirium is a neuropsychiatric disorder of attention and awareness that develops over a short time and fluctuates in severity. Although delirium has been extensively studied in intensive care units, the incidence of delirium in stroke units and its predictors in stroke patients need further investigation. The endpoints of our study were incidence of delirium in acute stroke and the risk factors that predispose to this condition. Methods: Patients were consecutively enrolled in a stroke unit from April to October 2020. Inclusion criteria were: age ≥18 years, acute stroke and National Institute of Health Stroke Scale (NIHSS) score ≥1 at the time of clinical assessment of delirium. Exclusion criteria were: transient ischemic attack; absence of neuroimaging evidence of brain lesion; cerebral venous thrombosis; subarachnoid hemorrhage; and clinical conditions requiring intensive care unit treatment. All patients were evaluated by means of Richmond Agitation‐Sedation Scale (RASS) and Confusion Assessment Method‐Intensive Care Unit (CAM‐ICU) scores at baseline, evaluations which were repeated within 72 h or when patients developed symptoms suggesting delirium. Results: The overall incidence of delirium was 36/120 (30%). Delirium was associated with aphasia (odds ratio [OR] 9.77; confidence interval [CI] 1.2–79.6), chronic obstructive pulmonary disease (COPD; OR 16.67; CI 1.1–263.0), deep Fazekas score (OR 5.05; CI 1.7–14.8), and physical restraint (OR 45.02; CI 1.4–1411.5). Diabetes was associated with a lower incidence of delirium (OR 0.04; CI 0.026–0.7). Conclusions: Nearly one‐third of patients (30%) had delirium in the acute phase of stroke. This finding supports the notion that delirium is a common complication of stroke. Delirium was associated with speech disorder, leukoencephalopathy, COPD and early use of physical restraint. Abstract : Delirium in stroke unit is frequent and is strongly associated with stroke‐specific risk factors. The strongest predictors of delirium are aphasia, leukoencephalopathy, chronic obstructive pulmonary disease, and the early use of physical restraint. Care‐related issues are relevant in precipitating delirium.